Relationship between service quality and customer satisfaction at Tabungan Haji Kuching / Fadzilah Ramlee - Ramlee, Fadzilah (2015)
“In Malaysia, there are several types of banking industries such as investment banks, commercial banks and Islamic banks" (Jayaraman, 2010). They represent as the primary mobiliser of funds and also being financial sources to support national economic activities. The customers are the main variables that will lead development of the banking industries. It is because, without the customers, banking industries could not grow up efficiently and effectively. In developing and increasingly competitive on banking industries, organization must establish something different in order to make them apart from the crowd. “There are some elements have been used in segmentation by banking industries such as convenience, product lines and customer service ” (Simpson, 2006). Besides that, organization also is focusing their attention on customer service which is means it is increasing customer loyalty and retention. In order to achieve the goal of increasing customer retention, the relationship between employees satisfaction who are responsible in being service provider, customer service quality which means the customer behaviors that those attitudes lead to and the customer satisfaction which the behaviors from customers has become important part of investigation.